7+(1+5n)+6+24n=13

Simple and best practice solution for 7+(1+5n)+6+24n=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+(1+5n)+6+24n=13 equation:


Simplifying
7 + (1 + 5n) + 6 + 24n = 13

Remove parenthesis around (1 + 5n)
7 + 1 + 5n + 6 + 24n = 13

Reorder the terms:
7 + 1 + 6 + 5n + 24n = 13

Combine like terms: 7 + 1 = 8
8 + 6 + 5n + 24n = 13

Combine like terms: 8 + 6 = 14
14 + 5n + 24n = 13

Combine like terms: 5n + 24n = 29n
14 + 29n = 13

Solving
14 + 29n = 13

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + 29n = 13 + -14

Combine like terms: 14 + -14 = 0
0 + 29n = 13 + -14
29n = 13 + -14

Combine like terms: 13 + -14 = -1
29n = -1

Divide each side by '29'.
n = -0.03448275862

Simplifying
n = -0.03448275862

See similar equations:

| 28=10+(-6x) | | 6x+2y-9(5x-4y)= | | -4(3y-10)+3(2y+7)= | | -15+7x=20 | | 25-(3x+2)=2 | | (8y-3)(2y+1)=0 | | 2x+2=3x-men | | 1/8(5y+65)=1/4(20+2y) | | x+3x+x/2-225 | | -5.9x-5.8=-5.5x-5.4 | | 7/10x=392 | | 6x^2-11x=-5 | | 5y-8-2y+7=0 | | 42=18-3x | | -2/3(3/2a-1)+5/6 | | 6x^2-11x=5 | | 9p+6=14+8p | | -3/4a=-5/8 | | 6(5/7+4/63) | | X(6x-11)=5 | | 4(x+2)+2(x-7)-3(x+1)= | | p=6-2q | | 1=-5(4x+2)+21x | | -1/3q=2/3 | | 8x-10=8x+11 | | -24=11v | | 5a+3-b+1= | | 2/3-1/8 | | 4=18+7x | | 1=(4x+2)+21x | | 2(a+b)+3(2b-4a)= | | 3x-12/6=-5 |

Equations solver categories